2021
DOI: 10.1002/gch2.202000119
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Selective Hydrolysis of Polyamides from Multicomponent Carpet Waste

Abstract: against landfills, and incineration does not retain the intrinsic material value of the polymeric materials which is a waste of resources. [6] Synthetic carpets usually consist of a multicomponent system, where several different polymeric materials constitute the fibers and backing, respectively. The advantage of the multicomponent system is the specific properties and performances of the different polymers. This is, however, a disadvantage when it comes to recycling, as sorting and separation become challengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Unlike PET, which can be readily hydrolyzed by base or hydrolase, 14 PA‐66 is resistant to light, abrasion, and strongly basic conditions. However, the amide bond of PA‐66 can be readily degraded into monomers under mild conditions with hydrolyzed acid 15–17 . In view of this, as shown in Figure 1A, the integrated system for PA‐66 upcycling contained several reaction steps: (i) H 2 SO 4 ‐catalyzed PA‐66 (Equation 1), (ii) hydrolysis product separation, (iii) KOH‐assisted filtered hydrolysate (Equation 2), and (iv) electroreforming of KOH‐assisted PA‐66 hydrolysate (Equation 3), including hexamethylenediamine (HMD) oxidation (Equation 4) and paired hydrogen evolution reaction (HER) (Equation 5).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike PET, which can be readily hydrolyzed by base or hydrolase, 14 PA‐66 is resistant to light, abrasion, and strongly basic conditions. However, the amide bond of PA‐66 can be readily degraded into monomers under mild conditions with hydrolyzed acid 15–17 . In view of this, as shown in Figure 1A, the integrated system for PA‐66 upcycling contained several reaction steps: (i) H 2 SO 4 ‐catalyzed PA‐66 (Equation 1), (ii) hydrolysis product separation, (iii) KOH‐assisted filtered hydrolysate (Equation 2), and (iv) electroreforming of KOH‐assisted PA‐66 hydrolysate (Equation 3), including hexamethylenediamine (HMD) oxidation (Equation 4) and paired hydrogen evolution reaction (HER) (Equation 5).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolysis reactions are commonly used for the chemical recycling of polyesters, such as poly­(ethylene terephthalate) (PET), and has also been applied recently for the closed loop recycling of long-chain polyesters . The hydrolysis of polyamides, however, is more complicated and often requires long reaction times and harsh conditions. , Microwave-assisted hydrolysis is a promising tool for the chemical recycling of polyamides with reduced reaction times and energy consumption. …”
Section: Resultsmentioning
confidence: 99%
“…Urška Češarek et al [128] found in their study of the chemical recycling of aliphatic polyamides that when HCl was used as an acid catalyst with external microwave radiation at 200 • C and a 1.25 HCl/amide molar ratio, PA-66 could be completely converted into constituent monomers in 10 min. Subsequently, Eva Bäckström et al [129] found that polyamide-6 (PA-6) and polyamide-66 (PA-66) would be selectively hydrolyzed by microwave-assisted hydrolysis of industrial multi-component polyamide-6 (PA-6)/ polyamide-66 (PA-66)/polypropylene (PP) carpets, which may provide new ideas for the separation and degradation of composite materials.…”
Section: Microwave-assisted Hydrolysismentioning
confidence: 99%